The The Effect of Foreign Debt, Labor Force, and Net Exports on Indonesia's Economic Growth in Period of 1986 Q1 - 2020 Q4 - Nur Annisa; N. Nairobi; Arivina Ratih Yulihar Taher (Universitas Warmadewa, 2022)
The purpose of this study is to analyze the effect of foreign debt, labor force, and net exports on economic growth in Indonesia. The data used is time-series data for the period 1986 first quarter to 2020 fourth quarter. The method used in this study is a qualitative descriptive method. The results of this study revealed that the foreign debt variable has a negative and significant effect on economic growth in Indonesia, while the labor force and net exports variables each have a positive and significant impact on economic growth in Indonesia. In addition, the results of the study showed that Indonesia's choice to choose foreign debt as capital to cover the budget deficit is not the right thing.